Misdiagnosed myocarditis in arrhythmogenic cardiomyopathy induced by a homozygous variant of DSG2: a case report - Liu, Xuwei; Zhang, Yue; Li, Wenjuan; Zhang, Qian; Zhou, Letao; Hua, Yimin; Duan, Hongyu; Li, Yifei (Frontiers in Cardiovascular Medicine, 2023)
Background Arrhythmogenic Cardiomyopathy (ACM) is an inherited cardiomyopathy that is rarely diagnosed in infants or young children. However, some significant homozygous or compound heterozygous variants would contribute to more severe clinical manifestations. In addition, the inflammation of the myocardium and ventricular arrhythmia might lead to misdiagnosis with myocarditis. Here, we describe an 8-year-old patient who had been misdiagnosed with myocarditis. And timely genetic sequencing helped to realize this case as a homozygous variant of DSG2-induced ACM. Case Presentation The proband of this case was an 8-year-old boy who initially presented with chest pain with an increased level of cTnI. Moreover, the electrocardiogram revealed multiple premature ventricular beats. Cardiac magnetic resonance reported myocardial edema in the lateral ventricular wall and apex, indicating localized injuries of the myocardium. The patient was primarily suspected of acute coronary syndrome or viral myocarditis. The whole exon sequencing confirmed that the proband had a homozygous variation on c.1592T>G of the DSG2 gene. This mutation site was regulated by DNA modification, which induced amino acid sequence changes, protein structure affected, and splice site changes. According to MutationTaster and PolyPhen-2 analyses, the variant was considered a disease-causing mutation. Then we used SWISS-MODEL to illustrate the mutation site of p.F531C. And the ensemble variance of p.F531C indicated the free energy changes after the amino acid changed. Conclusion In summary, we reported a rare pediatric case presenting as myocarditis initially, which transited into ACM during follow-up. And a homozygous genetic variant of DSG2 had been inherited in the proband. This study expanded the clinical features spectrum of DSG2-associated ACM at an early age. Also, the presentation of this case emphasized the difference between homozygous and heterozygous variants of desmosomal genes in disease progress. Moreover, the genetic sequencing screening would be much helpful in distinguishing unexplained myocarditis in children.